Chaos is in the eye of the beholder: unravelling a quasi-criticism of the Serbian citation index - Šipka, Pero (Sociološki pregled, 2021)
The article is a response to criticism published by Rajko Bukvić in Ekonomski vidici in the paper ‘On quality and visibility of social and economic sciences of Serbia’, more precisely in the section entitled Scandals directed by CEON/CEES: Does chaos rule in our (economic) periodic publishing? In this section, the author directly accuses CEON/CEES for producing chaos in social sciences in Serbia by “excluding” many journals from its database called the Serbian Citation Index (SCIndeks). According to the author, CEON/CEES, after the termination of the financial support by the Serbian ministry responsible for science, blackmailed journal publishers by accepting for indexation only those willing to pay a fee for content maintenance. The author also claims that excluding three journals published by the Faculty of Organizational Sciences (FON), University of Belgrade, was illegal and scandalous. He adds to his allegations against SCIndeks several other unfounded, less important issues, supported by some serious unwarranted ethical accusations against its publisher. In this response, it is demonstrated that all accusations are fabricated and malicious. The alleged exclusion of formerly indexed journals was explained as a fully justified action of “non-inclusion” of journals unwilling to pay the necessary service fee after the forced transition of SCIndeks’s business model from a government-sponsored to the journals-sponsored (“diamond open access”, Ševkušić, Kosanović, & Šipka, 2020). Also, the suspension of the journals published by FON was a legitimate action aimed at protecting SCIndeks from a publisher who turned out to be untrustworthy, as demonstrated by the act of concealing the blatant plagiarism in the PhD thesis of the current Minister of Finance in the Serbian Government. The decision was reinforced by the discovery of a history of publishing in predatory journals by many members of the journals’ editorial boards, the Dean’s Collegium, and the Faculty Council. The author of the criticism is unmasked as lacking not only the basic knowledge on scientometrics, but also research and ethic integrity.